VARIASI WAKTU EKSTRAKSI DAN JENIS ASAM PADA PROSES PRODUKSI GELATIN TULANG IKAN NILA (Oreochromis niloticus) - Neneng Suliasih; Nabella Respatyana (Department of Food Technology, Universitas Pasundan, Bandung, 2020)
The purpose of this research is to find out determine the effect of the most effective extraction time and to determine the effect of the most effective type of acid in the production process of gelatin bone of tilapia fish. This research was using by Split Plot Design (SPD) with 3 times replication, so make 27 experiments were obtained. For main plot is extraction time (4 hours, 5 hours and 6 hours) and subplot is type of acid (4% chloride acid, 3% acetic acid and 6% citrate acid). Response in this research is physical response such as gel gelatin strength, viscosity and rendement total, chemical response such as pH, protein content and ash content and test of bone gelatin of tilapia fish with commercial gelatin. The main research result showed that the extraction time had significant effect on gelatin gel strength, gelatin viscosity, gelatin rendement, acidity degree (pH) of gelatin, gelatin protein content and gelatin ash content. Types of acid had significant effect on gelatin gel strength, gelatin renedement, acidity degree (pH) of gelatin, gelatin protein content and gelatin ash content, and interaction of time of extraction and type of acid had significant effect on gelatin gel strength, gelatin viscosity, gelatin rendement, acidity degree (pH) of gelatin, gelatin protein content and gelatin ash content to the extraction process of bone gelatin of tilapia fish. Based on the comparative test, the characteristics of gelatin of tilapia bone that close to commercial gelatin are a3b2 treatment (6 hours of extraction time, 3% acetic acid) with the result of gelatin gel strength 132,93 bloom; viscosity 5,83 cP; the amount of rendement 16,94; pH 6,10; protein content 83,62%; and ash content of 0.64%.